Geneza i ewolucja subkultury pseudokibiców jako ważnego determinantu zagrożenia przestępczością w aglomeracjach - Czop, Andrzej; Juszczak, Agnieszka
Authors, who have had great deal of practice in counteracting the violence of hooligans have found that they are one of the major threats that occur in public spaces, especially in large cities. They are the perpetrators of serious collective disturbance of order and security, and to restore peace the police is forced to use a significant force and means of direct coercion.
Keywords: szalikowcy; struktura pseudokibiców; bezpieczeństwo publiczne; przestępczość zorganizowana; ultras; hooligan structure; security; organized crime